2020
DOI: 10.1371/journal.pgen.1008691
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of CFAP57, a protein required for the asymmetric targeting of a subset of inner dynein arms in Chlamydomonas, causes primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is characterized by chronic airway disease, reduced fertility, and randomization of the left/right body axis. It is caused by defects of motile cilia and sperm flagella. We screened a cohort of affected individuals that lack an obvious axonemal defect for pathogenic variants using whole exome capture, next generation sequencing, and bioinformatic analysis assuming an autosomal recessive trait. We identified one subject with an apparently homozygous nonsense variant [(c.1762C>T)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 105 publications
0
32
0
Order By: Relevance
“…Also, human DNAH2 gene, a potential orthologue of Chlamydomonas IDA f/I1β HC ( DHC10 ) (Kollmar, 2016) is a candidate gene of one type of the teratozoospermia, multiple morphological abnormalities of the sperm flagella (MMAF) (Li et al, 2019). In addition, defects in human DNAH6 gene, a potential orthologue of Chlamydomonas DHC7 (IDA g) or minor IDA DHC3 (Bustamante‐Marin et al, 2020; Kollmar, 2016), have been reported to cause azoospermia, suggesting the important role of IDA g in spermatogenesis and sperm motility (Gershoni et al, 2017; Y. Li et al, 2016).…”
Section: Subunits Of Idas Identified In Chlamydomonas Their Potential Functions and Homologs/orthologues In Other Eukaryotesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, human DNAH2 gene, a potential orthologue of Chlamydomonas IDA f/I1β HC ( DHC10 ) (Kollmar, 2016) is a candidate gene of one type of the teratozoospermia, multiple morphological abnormalities of the sperm flagella (MMAF) (Li et al, 2019). In addition, defects in human DNAH6 gene, a potential orthologue of Chlamydomonas DHC7 (IDA g) or minor IDA DHC3 (Bustamante‐Marin et al, 2020; Kollmar, 2016), have been reported to cause azoospermia, suggesting the important role of IDA g in spermatogenesis and sperm motility (Gershoni et al, 2017; Y. Li et al, 2016).…”
Section: Subunits Of Idas Identified In Chlamydomonas Their Potential Functions and Homologs/orthologues In Other Eukaryotesmentioning
confidence: 99%
“…IDA d and e may be partially replaced by minor IDAs DHC11 and DHC4 in the proximal portion of the axonemes (Bui et al, 2012). Also, replacement of IDA g by DHC3 was proposed in Bustamante‐Marin et al, (2020). DMT1 has unique organization of IDAs throughout the axonemes (Bui et al, 2012; Hoops & Witman, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a mutation in the CFAP57 gene has been identified to be associated with PCD. This protein is involved in IDA assembly, and its absence resulted in a reduced beating frequency of cilia with an altered beating pattern [ 153 ].…”
Section: Structure and Composition Of The MCC Apparatus In Humansmentioning
confidence: 99%
“…Mutations in ODA docking complex genes usually cause a complete absence of outer dynein arms and static cilia [168]. Mutation in CFAP57, an inner arm assembly component, causes a mild respiratory phenotype, where ciliary movement shows heterogeneous waveforms with reduced frequency, and patients do not show any defect in the ultra-structure of the cilia [173]. PCD patients with only inner dynein arm defects are difficult to diagnose; often, repeat collection of samples for EM and ciliary beat pattern analysis is required [174].…”
Section: Axonemal Dynein Related Ciliopathiesmentioning
confidence: 99%